MENGEMBANGKAN SIKAP CINTA ALLAH DAN RASUL MELALUI METODE KISAH PADA ANAK USIA DINI - Masganti Masganti (JURNAL RAUDHAH, 2016)
Attitude marking believe in early childhood include; imitative,unreflective, verbalis and ritualis, wondering, anthromorphis, andegocentric. Wondering cause children aspire after to listen storys related toidol figures of[is including Allah and of Rasul-Nya. They show to wonderwith storys. Story method can develop attitude love Allah and of Rasul [at]age child early, because passing heard story, they will grow to feel tomarvel able to become base of growing of attitude love to Allah and HisRasul.Kata Kunci:Cinta Allah dan Rasul-Nya, Metode Kisah, Anak Usia Dini.